Revitalizing Islamic Religious Education: Integration Of Project-Based Learning To Generate Student Creativity - Muhammad Fahmi Hanan; Zaenal Abidin (Institut Agama Islam An-Nawawi Purworejo, 2024)
This research aims to measure the applicability of the PjBL model in PAI subjects regarding caring for and praying for corpses, as well as investigating how student creativity can be developed as a result of implementing this learning model. The research was conducted evaluatively, namely by observing the implementation of the model. The student creativity variable is carried out by product assessment. The sample consisted of two classes with 62 students comprised of 26 male students and 36 female students aged between 16-17 years at SMA Muhammadiyah 1 Klaten. The instruments used in this research were (1) an observation sheet, (2) a product assessment questionnaire, and (3) an interview sheet. The observation sheet is used to observe the implementation of the model. The average of the observation data is calculated to conclude the applicability of PjBL implementation. Student creativity data from the questionnaire results was analyzed by calculating the average score for each aspect. The data from the interviews was qualitative and analyzed descriptively. The results show that the learning model was applied well in the material on caring for and praying for corpses. Overall, students have high creativity after learning. Educators need to design and implement projects that are academically relevant and enhance students' creative skills.